ABOUT MODERN SCIENTIFIC CONGRESSES AND CONFERENCES IN OUR SPECIALTY - V. V. Borisov (Вестник урологии, 2016)
We all regularly participate in scientific congresses, conferences and forums organized by urologists and doctors related specialties. It is known that new - it is often forgotten old. On the basis of their memories present in the article how such events occasion in the recent past, what does not satisfy the present and that can be a positive change in the future.